Hospital costs associated with psychiatric comorbidities: a retrospective study - Jan Wolff; Thomas Heister; Claus Normann; Klaus Kaier (BMC, 2018)
Abstract Background Psychiatric comorbidities are relevant for the diagnostic and therapeutic regimes in somatic hospital care. The main aim of this study was to analyse the association between psychiatric comorbidities and hospital costs per inpatient episode. A further aim was to discuss and address the methodological challenges in the estimation of these outcomes based on retrospective data. Methods The study included 338,162 inpatient episodes consecutively discharged between 2011 and 2014 at a German university hospital. We used detailed resource use data to calculate day-specific hospital costs. We adjusted analyses for sex, age, somatic comorbidities and main diagnoses. We addressed potential time-related bias in retrospective diagnosis data with sensitivity analyses. Results Psychiatric comorbidities were associated with an increase in hospital costs per episode of 40% and an increase of reimbursement per episode of 28%, representing marginal effects of 1344 € and 1004 €, respectively. After controlling for length of stay, sensitivity analyses provided a lower bound increase in daily costs and reimbursement of 207 € and 151 €, respectively. Conclusion If differences in hospital costs between patient groups are not adequately accounted for in DRG-systems, perverse incentives are created that can reduce the efficiency of care. Therefore, we suggest intensifying the inclusion of psychiatric comorbidities in the German DRG system. Future research should investigate the appropriate inclusion of psychiatric comorbidities in other health care systems' payment schemes.